Daclatasvir-Sofosbuvir Combination Therapy with or without Ribavirin for Hepatitis-C Virus Infection: An Experience from a Tertiary Care Hospital, Pakistan - Ahmed, Abeera; Rafique, Iffat; Sana, Fatima; Khurshed, Sabeen; Yousef, Shagufta; Khan, Aysha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the impact and effectiveness of a pan-genotypic Directly Acting Antiviral (DAA) based regimen for patients with chronic Hepatitis-C (HCV) infection in our setup.Study Design: Cross-sectional study.Place and Duration of Study: Departments of Pathology and Medicine, Combined Military Hospital, Malir, Karachi, from Dec 2019 to Jan 2021.Methodology: Sofosbuvir and Daclatasvir were administered orally at 400mg and 60mg daily, respectively, with or without Ribavirin to treatment-naïve and treatment-experienced adult patients with chronic HCV infection. End-of-treatment response and Sustained virological response were determined among these patients by monitoring viral load using quantitative HCV RNA PCR and various genotypes.Results: Of the 59 patients, 39(66%) patients received sofosbuvir (SOF)+Daclatasvir (DCV), 12(20.3%) patients were placed on SOF+Ribavirin (Rib) and 8(13.5%) were given triple regime of SOF+DCV+Rib for 12 and 24 weeks respectively. Most of our patients were females, 32(54.23%), with a mean age of 31±17 years. Forty-eight patients (81.35%) were infected with genotype 3, followed by genotype 1 and 2, respectively. The rapid viral response was noted after four weeks of therapy among 27(45.76%) patients. The sustained viral response was noted in 38(64.40%) and 21(35.59%) patients after 12 and 24 weeks, respectively. The end-of-treatment response was observed in 40(67.8%) patients.Conclusion: Direct-acting antiviral-based regimens have shown favourable results with fewer adverse effects in our patients.